2008
DOI: 10.3354/meps07480
|View full text |Cite
|
Sign up to set email alerts
|

Spawning, larval abundance and growth rate of Sardinops sagax off southwestern Australia: influence of an anomalous eastern boundary current

Abstract: The temporal and spatial distributions of sardine Sardinops sagax eggs and larvae off the oligotrophic southwestern coast of Australia were examined and related to gonadosomatic index, daily growth rates of larvae and regional biological oceanography. Seasonal environmental cycles were established from remotely sensed sea surface temperature and chlorophyll concentration, wind and sea surface height data. Sardine egg and larval distributions were determined from regular transect surveys and annual grid surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…Surveys of eggs and larvae of the economically important sardine, Sardinops sagax, show clear alongshore connectivity on the shelf during winter, with eggs more abundant in the north (Abrolhos) and larvae distributed further south towards Geographe Bay (Muhling et al 2008b). …”
Section: Retention V Dispersal and Their Relations With Fish Larvaementioning
confidence: 99%
“…Surveys of eggs and larvae of the economically important sardine, Sardinops sagax, show clear alongshore connectivity on the shelf during winter, with eggs more abundant in the north (Abrolhos) and larvae distributed further south towards Geographe Bay (Muhling et al 2008b). …”
Section: Retention V Dispersal and Their Relations With Fish Larvaementioning
confidence: 99%
“…Satellite-derived SST data have become a widely used tool for monitoring changes in ocean temperature driven by climate change and have been incorporated into a myriad of biological models and studies (e.g. Littaye et al 2004, Zainuddin et al 2006, Muhling et al 2008. Temperature is a key factor controlling the distribution of species and physiological processes (Schils & Wilson 2006, O'Connor et al 2007, Byrne et al 2009, Staehr & Wernberg 2009, and easily accessible temperature data for the global ocean has facilitated considerable progress in our understanding of broad-scale biological patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pilchards <2 years old that probably originated from the Perth region (Muhling et al 2008a) have been found in Geographe Bay (Gaughan et al 2001b), ~150 km south of Penguin Island. In addition, during a strong summer Leeuwin Current, the normally enhanced upwellings associated with the Capes Current in the south-west (Hanson et al2005), are likely to be less productive.…”
Section: Discussionmentioning
confidence: 99%
“…It is no surprise then that peak spawning activity of small pelagic clupeid fish, such as pilchard (Sardinops sagax) and anchovy (Engraulis australis), generally occurs when offshore transport is low and larval food concentrations are high (Somarakis et al 2006;Muhling et al 2008a). These fish species, as well as sandy sprat (Hyperlophus vittatus), blue sprat (Spratelloides robustus) and garfish (Hyporhamphus melanochir), comprise the majority of the diet of the penguins from Penguin Island (Klomp and Wooller 1988a;Wienecke 1989;Wooller et al 1991;Connard 1995;Bradley et al 1997;Murray et al 2011).…”
Section: Introductionmentioning
confidence: 99%